E-book Fisika Berbasis CTL untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Peserta Didik di SMA - Prasetyo Fitriadi; Ivandra Immanuela Latumakulita; Jumadi Jumadi; Warsono Warsono (Jurnal Penelitian Pendidikan IPA, 2022)
This article reports on the validity of CTL-based physics e-books and the effectiveness of media developed for student problem-solving skills. This research is development research and uses a quantitative approach. The subjects of this research were 17 students of class X science class and 26 students of class X social class at one of the senior high schools in Yogyakarta as the implementation class and modeling classes. The results of this study indicate that the development of a CTL-based physics e-book on simple harmonic oscillation material is feasible in terms of expert validation results where the average total validation score is 3.75 with a very high category. The use of a CTL-based physics e-book in the learning process is able to have a significant influence on improving the problem-solving skills of students in both classes, which is indicated by the value of sig. (2-tailed) of 0.00 both for modeling and implementation classes which are smaller than the alpha value of 0.05.